45. OUTPATIENT MANAGEMENT OF TYPE II DIABETIC OUTPATIENTS IN BINH XUYEN DISTRICT HEALTH CENTER IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to evaluate the outpatient management of type II diabetic outpatients in Binh Xuyen District Health Center (DHC) in 2022.Methods: This cross-sectional study (quantitative method) was conducted within 3 months (April-July/2022) at Binh Xuyen DHC. Quantitative data was collected by face-to-face interview for a convenient selected 215 type II diabetic outpatients. Data was analyzed using SPSS ver 25.0.Findings: Screening and diagnosis of type II diebetes: The activity was implemented yearly with the increased number of newly confirmed diabetic patients (210 in 2020 and 182 in 2021). Outpatient medical records was managed by both methods (writtent medical records and electronic records). Planning, monitoring and evaluating the treatment results were done well with regular follow-up visits for all outpatients. Information – Education – Communication activities were performed well by main communication channels including health providers (88.4%), leaflets, booklets, etc. (33%).Conclusions: We recommended to strengthen measures for training and recruiting health providers, improve the supply of one-time equipment. Develop electronic health information management to support the management and treatment of type II diabetic oupatients.
Keywords: Diabetes; outpatient management; type II diabetic outpatients; Binh Xuyen District Health Center